Phylogeny and adaptative evolution to chemosynthetic habitat in barnacle (Cirripedia: Thoracica) revealed by mitogenomes - Gan, Zhibin; Jones, Diana S.; Liu, Xinming; Sui, Jixing; Dong, Dong; Li, Xinzheng (Frontiers in Marine Science, 2022)
Thoracican barnacles represent a unique group that has evolved in parallel identical somatotype s (sessile, stalked and asymmetric) in both normal and chemosynthetic environments. Hydrothermal vents and methane seeps are typical extreme deep-sea chemosynthetic habitats for marine macrobenthos. Characterizing the evolutionary history and adaptive strategy of barnacles is fundamentally important for understanding their origin, speciation, and diversification. Herein, we performed a series of phylogenetic analyses focusing on the mitochondrial genomes of the main extant barnacle lineages. Phylogenetic inferences and topology tests contradict the view of the sister relationship between verrucomorphs and balanomorphs, instead revealing that pollicipedids, calanticids and balanomorphs share common ancestor. Selective pressure analyses indicate that the two barnacle lineages of chemosynthetic ecosystems exhibit similar patterns in their evolution of adaptive characters, but have diverse and specific positive substitution sites of mitogenomes. Divergence times suggest that chemosynthetic barnacles originated in the Cenozoic, coinciding with the origins of other metazoan animals in chemosynthetic habitats as well as the Paleogene mass extinction and oceanic anoxic events. It is reasonable to suppose that ecological niche vacancy, sitotaxis, gene specificity in adaptive stress responses, and the subdivision of the ecological niche contributed to the origin and diversification of barnacles in chemosynthetic ecosystems.